Daily System Check of Electronic Position Systems - Lapine, Lewis A. (The International Hydrographic Review, 2015)
The use of electronic navigation systems onboard NOS survey vessels necessitates one or more daily system checks to ensure the operational precision of the systems. In most instances, a position fix by visual methods is used for the daily check. The paper will first establish precision estimates for four fundamental measurements used in visual fixes and then present a discussion of six basic visual methods for daily system checks. The visual methods will be examined for their individual merits, drawbacks and estimated precision.